2018
DOI: 10.1007/s00424-018-2183-3
|View full text |Cite
|
Sign up to set email alerts
|

The renal vasodilatory effect of prostaglandins is ameliorated in isolated-perfused kidneys of endotoxemic mice

Abstract: Endotoxemia-related acute kidney injury (AKI) is associated with increased formation of prostaglandins, which may serve as a compensatory mechanism to maintain renal function. We hypothesized that an increase of renal EP or EP receptors and/or a downregulation of renal EP and EP receptors enhances PGE-induced renal vasodilatation. Injection of lipopolysaccharide (LPS; 3 mg/kg i.p.) increased microsomal prostaglandin E synthase (mPGES)-1 and prostacyclin synthase expression, whereas mPGES-2 expression was unalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
1
3
1
Order By: Relevance
“…In contrast to findings of the present study, one prior report showed that iloprost increases the basal flow (obtained under un‐precontracted conditions) in perfused kidneys, especially those of mice with endotoxemia 49 . Another study also revealed that bolus injection of PGI 2 causes contractile activity, which is, however, followed by a relaxation under perfusion with another vasoconstrictor methoxamine 50 .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to findings of the present study, one prior report showed that iloprost increases the basal flow (obtained under un‐precontracted conditions) in perfused kidneys, especially those of mice with endotoxemia 49 . Another study also revealed that bolus injection of PGI 2 causes contractile activity, which is, however, followed by a relaxation under perfusion with another vasoconstrictor methoxamine 50 .…”
Section: Discussioncontrasting
confidence: 99%
“…The prostaglandins, once formed, are released quickly out of cells, and are assumed to work in the vicinity of their sites of production as a result of their chemical and metabolic instability. Several studies have confirmed that PGE2 plays an important role in the occurrence and development of AKI [36,41,42]. Consistent with previous studies, our results showed that, during H 2 O 2 -induced ferroptosis in HK-2 cells, PGE2 content in supernatant increases, and PGE2 pathway changes were detected during ferroptosis in HK-2 cells.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have reported an association between AKI and the rise of prostaglandins. PGE2 pathway can regulate the therapeutic effect of AKI induced by IRI in mice [36,37]. However, it is not clear whether the PGE2 pathway is associated with ferroptosis in AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Coincidentally, LPS-induced kidney injury model revealed increased PGE2 level indicating PGE2 may be a risk factor for kidney injury [41]. However, Meurer et al [42] indicated that PGE2 could maintain GFR and renal perfusion by dilating the renal afferent arteriole. In addition, their study indicated elevated expressions of PGE2 and vasodilatation in endotoxemia-related acute kidney injury by injecting LPS in mice.…”
Section: Discussionmentioning
confidence: 99%